The Telegraph Equation and Its Solution by Reduced Differential Transform Method - Vineet K. Srivastava; Mukesh K. Awasthi; R. K. Chaurasia; M. Tamsir (Modelling and Simulation in Engineering)
One-dimensional second-order hyperbolic telegraph equation was formulated using Ohm’s law and solved by a recent and reliable semianalytic method, namely, the reduced differential transform method (RDTM). Using this method, it is possible to find the exact solution or a closed approximate solution of a differential equation. Three numerical examples have been carried out in order to check the effectiveness, the accuracy, and convergence of the method. The RDTM is a powerful mathematical technique for solving wide range of problems arising in science and engineering fields.